Telaah Filsafat Ketuhanan dalam Hulul, Ittihad, dan Wahdatul Wujud sebagai Ekspresi Transendensi Spiritual dalam Tasawuf Falsafi - Pranoto, Ahmad Hadi; Nurhuda, Abid; Bin Engku Ab Rahman, Engku Shahrulerizal (LPPM Sekolah Tinggi Ilmu Ekonomi 45 Mataram, 2025)
This study discusses in depth the dynamics of philosophical Sufism with a focus on the concepts of hulul, ittihad, and wahdatul wujud as the pinnacle of human ontological awareness of God. These three concepts represent the highest phase of spiritual journey where the boundaries between the divine and the human merge into a unity of existence. This study uses a qualitative-philosophical approach with a Sufi hermeneutic model to interpret the inner meaning of classical Sufi texts such as the works of al-Hallaj and Ibn 'Arabi. The data were analysed through three stages of interpretation: exoteric (textual), esoteric (symbolic), and transcendental (ontological). The results show that philosophical Sufism not only contains metaphysical aspects, but also epistemological and spiritual values that build a dynamic relationship between reason and intuition. Through an understanding of hulul, ittihad, and wahdatul wujud, humans are guided to realise that their existence is a reflection of divine reality. Thus, this study affirms that the unity of existence is not the loss of human existence, but rather the unification of consciousness in the presence of an absolute and comprehensive God.